Potential Spillover Educational Effects Of Cancer-Related Direct-To-Consumer Advertising On Cancer Patients’ Increased Information Seeking Behaviors: Results From A Cohort Study - Tan, Andy SL (2014)
Spillover effects of exposure to direct-to-consumer advertising (DTCA) of cancer treatments on patients’ general inquiry about their treatments and managing their illness are not well understood. This study examines the effects of cancer patients’ exposure to cancer-related DTCA on subsequent health information seeking behaviors from clinician and non-clinician sources (lay media and interpersonal contacts). Using a longitudinal survey design over three years, data was collected from cancer survivors diagnosed with colorectal, breast, or prostate cancer who were randomly sampled from the Pennsylvania Cancer Registry. Study outcome measures include patients’ information engagement with their clinicians and information seeking from non-medical sources about cancer treatment and quality of life issues, measured in the second survey. The predictor variable is the frequency of exposure to cancer-related DTCA since diagnosis, measured at the round 1 survey. The analyses utilized lagged weighted multivariate regressions and adjusted for round 1 levels of patient-clinician engagement, information seeking from non-medical sources, and confounders. Exposure to cancer-related DTCA is associated with increased levels of subsequent patient-clinician information engagement (B=.023, 95%CI=.005 to .040, p=.012), controlling for confounders. In comparison, exposure to DTCA is marginally significant in predicting health information seeking from non-clinician sources (B=.009, 95%CI=−.001 to .018, p=.067). Cancer-related DTCA has potentially beneficial spillover effects on health information seeking behaviors among cancer patients. Exposure to DTCA predicts (a little) more patient engagement with their physicians.